Zolmitriptan Intranasal Spanlastics for Enhanced Migraine Treatment; Formulation Parameters Optimized via Quality by Design Approach - Asmaa Saleh; Maha Khalifa; Seham Shawky; Amjaad Bani-Ali; Heba Eassa (MDPI AG, 2021)
Zolmitriptan is a potent second-generation triptan prescribed for migraine attacks. It suffers low bioavailability (40%) after oral administration due to the hepatic first-pass metabolism. Spanlastics are surfactant-based elastic vesicular drug carrier systems. This study aimed to design and optimize intranasal spanlastic formulations as an alternative approach that directly targets brain delivery, enhancing its bioavailability and avoiding the first-pass effect. The quality by design approach was applied to correlate the formulation parameters (Span 60 and Tween 80 concentrations) and critical quality attributes (entrapment efficiency (EE%) and particle size). Spanlastic formulations were designed based on response surface central composite design and prepared via an ethanol injection method. Designed formulations were characterized by EE% and particle size measurements to select the optimized formula (with a combination of small particle size and high EE%). The optimized formula was further subjected to transmission electron microscopy, zeta potential measurement and ex vivo permeation study. The optimized formulation showed a particle size of 117.5 nm and EE% of 45.65%, with a low percentage of error between the observed and predicted values. Seventy percent of zolmitriptan was permeated through the nasal membrane within 30 min, and it completely permeated within 2 h with a significantly higher steady-state flux compared to plain gel. This study introduced a successful and promising intranasal formulation suitable for further brain delivery analysis.